Exploring Socioeconomic Disparities in Adults' Interactions with the Digital Food Environment: A Qualitative Study. - Molina Carrasco, Paulina; Gómez San Carlos, Natalia; Rodríguez Osiac, Lorena; Egaña Rojas, Daniel; Franch Maggiolo, Carolina; Gálvez Espinoza, Patricia (Inquiry (00469580), 2026)
The digital food environment is relevant for public health, as it shapes food access, promotion, and consumption. However, evidence on how different socioeconomic groups engage with this environment is limited. This study aimed to compare how adults from high- and low-socioeconomic status (SES) neighborhoods in Santiago, Chile, interact with the digital food environment. This qualitative, cross-sectional study conducted 11 focus groups with 78 adults from high- and low-SES neighborhoods. Data were analyzed using inductive reflexive thematic analysis. Two themes and 6 subthemes emerged. (1) Digital food environment as a space of access, consumption, and social differentiation : SES shaped the nature of digital food engagement. High-SES participants described routine use of online platforms to purchase meals and groceries, including healthier options. Low-SES participants engaged sporadically, driven by promotions and support from younger relatives. (2) Digital food environment as a communicative and affective space of influence : Participants reported exposure to unhealthy food advertising. High-SES individuals demonstrated greater awareness of targeted marketing and employed strategies to avoid ads. In contrast, low-SES participants tend to adopt a passive stance, valuing online information for economic reasons. Motivations also diverged: high-SES adults sought content related to self-care and healthy eating, whereas low-SES adults looked mainly for discounts or cheaper options. These findings highlight the interaction with the digital food environment is widespread among adults, showing disparities by SES. Findings underscore the need for targeted policies, including regulating digital marketing, promoting digital literacy, reducing socioeconomic disparities, and fostering healthier digital food environments.